WEBSITE-BASED COMPETENCE CERTIFICATION INFORMATION SYSTEM USING RAPID APPLICATION DEVELOPMENT (RAD) METHOD - Zidny Fahma Ilmy Gorby; Cepi Ramdani; Khairun Nisa Meiah (Informatika, Universitas Jenderal Soedirman, 2022)
Information system is a series of information systems that are overall and organized and rationally capable of transforming data into information. Competency Test Place (TUK) is a unit implementing competency standard testing, competency certification in a professional field and has responsibility for the implementation, guidance and development of competency standards and competency certification. Based on the results of interviews with the TUK unit manager, there are several obstacles in their services, namely, the certification registration process which has not been effective in serving prospective competency test participants, then certification information related to certification is still difficult for students to obtain directly. Based on these problems, it is necessary to have a Competency Certification information system that has a function as a medium for sharing information as well as a media for registration of certification. This study aims to build a Certification Information System and measure the level of conformity. The method that will be used in this research is RAD (Rapid Application Development). RAD was chosen because this model emphasizes the short development cycle of software development. UAT Operational Acceptance Testing was chosen because the level of acceptance of a system by users can be a benchmark for assessing the acceptance of an information technology by users and requires users to use the system or software that has been created. The test results using Operational Acceptance Testing type UAT on the system have obtained valid results which are accepted by 24 respondents who have tried the competency certification information system.